The Philosophy of Rabindranath Tagore - Haque, University of Dhaka, Bangladesh, Kaiser (Asiatic: IIUM Journal of English Language and Literature, 2010)
This paper aims to provide a comprehensive analytic perspective on Rabindranath Tagore as a thinker, taking on board his views on metaphysics and mysticism, as well as on more down-to-earth matters such as political theory and gender relations. Starting with Tagore’s well-known debate with Einstein over the nature of truth, it pinpoints the specific traits of his metaphysical idealism, refuting rival interpretations like that of William Radice. The question of Tagore’s mysticism and his connection with the Bauls of Bengal is next considered in the light of the psychoanalytic theories of Sudhir Kakar. The connection between Tagore’s metaphysics and his brand of feminism is explored. Finally, Tagore’s critique of nationalism is explored in the light of Ashis Nandy’s ideas, and by making a comparative study of Tagore and Nietzsche.